Surrender to the earl - Callen, Gayle (Avon romance., 2013)
Audrey Blake's plan to take ownership of property rightfully hers unravels quickly when Robert, the man she asks to help her, insists they pretend to be engaged. Duty may have brought Robert to Audrey's doorstep, but he yearns to convince her that they could both benefit from making it real.